Investigation of high flow nasal cannule efficiency with electric impedance tomography based parameters in COVID-19 adults patients: a retrospective study - Öner, Özlem; Ergan, Begum; Kizil, Ayse Sezin; Gurkok, Mehmet Cagatay; Dugral, Esra; Gökmen, Necati (PeerJ, 2023)
Background/Aim This study aimed to investigate the effects of oxygen therapy using a high flow nasal cannula (HFNC) on patients diagnosed with COVID-19 Acute Respiratory Distress Syndrome (C-ARDS) by utilizing electrical impedance tomography (EIT)-based parameters. Materials and Methods Oxygen therapy was administered to the patients at two different flow rates and two different positions: T0—baseline measurements were taken in the supine position before any therapy was initiated. T1—HFNC was administered in the supine position with a flow rate of 30 L/min. T2—HFNC was administered in the supine position with a flow rate of 50 L/min. T3—HFNC was administered in the prone position with a flow rate of 30 L/min. T4—HFNC was administered in the prone position with a flow rate of 50 L/min. EIT-based parameters (global inhomogeneity index (GI index), center of ventilation (CoV), regional ventilation delay index (RVD index), region of interest ratio (ROI ratio)), as well as respiratory and hemodynamic parameters of the patients, were recorded from the database. Results A total of twenty patients were included in this retrospective observational study. The mean age of the included patients was 64.3 ± 10.6 years. Statistically significant differences were observed in the measurements of GI index, CoV, RVD index, ROI ratio, PaO2/FiO2 ratio, respiratory rate, and mean arterial pressure parameters across different time intervals (p < 0.005). Pairwise comparisons of EIT parameters and measurements of respiratory and hemodynamic parameters at five different time points revealed statistically significant differences. For the GI index, significant differences were observed between the mean measurements taken at T0–T1, T0–T2, T0–T3, T0–T4, T1–T3, T1–T4, T2–T3, T2–T4, and T3–T4 time intervals (p < 0.05). Regarding CoV, significant differences were found between the mean measurements taken at T0–T3, T1–T3, T2–T3, and T3–T4 time intervals (p < 0.05). Additionally, for the ROI ratio, significant differences were observed between the measurement averages taken at each time interval (p < 0.05). Conclusion Our findings suggest that prone positioning during the management of C-ARDS patients leads to improved lung homogeneity, as indicated by EIT parameters. However, further research is required to enhance the visualization of ventilation using EIT.
Keywords: Covid-19; High flow nasal cannule; Efficiency; Electric impedence tomography